THE ISOTOPIC COMPOSITION OF HYDROGEN IN NOMINALLY ANHYDROUS MANTLE MINERALS - Bell D.R.; Ihinger P.D. (My University, 2000)
The common, nominally anhydrous minerals of the Earth's mantle are an important reservoir for hydrogen in the Earth's interior due to their ability to incorporate hydroxyl in trace quantities. We present measurements of the isotopic composition (D/H ratio) of hydrogen from upper-mantle derived garnet, enstatite and augite employing a two-step extraction procedure with infrared spectroscopic monitoring of OH removal from the samples. Raw δD values of all samples range from -80 to -130%%, and blank-corrected δD of high-purity separates with <50% blank contribution to the measured gas lie in the range -92 to -113%%. These δD values, together with predictions of fractionation behavior from IR spectroscopic systematics, suggest that the D/H ratio of the nominally anhydrous mineral reservoir may differ from that of other mantle hydrogen in being relatively depleted in deuterium. To the extent that nominally anhydrous minerals control the distribution of water between the Earth's hydrosphere and mantle, isotopic fractionations between OH in these minerals and hydrous melts or fluids may contribute to the large D/H fractionation between the mantle and the hydrosphere.